Lower limb lymphedema mimicking as elephantiasis in intravenous drug user - Aryan, Shubham; Singh, Mandeep; Sharma, Chavi; Khutan, Himanshu; Chahal, Jasmeen; Kumar , Naveen (International Journal of Advances in Medicine, 2024)
India been the population of over a billion, it is estimated that 62.5 million people use alcohol, 8.75 million use cannabis, two million use opiates, and 0.6 million use sedatives or hypnotics. Intravenous (IV) drug abuse is fairly spreading throughout the country. Rapid urbanization and migration to metro cities have led to disturbance in the social life render an individual more vulnerable to stresses and strain of modern life and with easy availability of drugs, sharing needle, peer pressure are also among the commonest reason for exponential rise of intravenous drug user (IVDU) especially among the young generation. IV drug abuse is one of most serious and social evil, prevailing in our society that leads to number of infections from local cutaneous infections to dreadful like human immuno-deficiency virus (HIV) which in turn not only increase the morbidity but mortality as well. Here we have patient who had history of IV drug injection to lower limb that led to chronic lower limb swelling which on further investigation turns out to be grade IV lymphedema.